SKRINING ANTIKANKER MELALUI PENDEKATAN UJI TOKSISITAS TERHADAP LARVA UDANG (Artemia salina Leach) SERTA IDENTIFIKASI GOLONGAN SENYAWA AKTIF PADA BUAH PLUM (Prunus domestica L.) - Ni Made Susita Pratiwi; I Made Dira Swantara; Ni Luh Rustini (Jurnal Kimia (Journal of Chemistry), 2015)
Isolation and identification of toxic compounds from ethanol extract of Prunus domestica L. have been conducted. Extraction of 1000 gr of plum fruit produced 128,75 g concentrated ethanol extract. The results of toxitcity tests of the extract using Artemia salina L. larvae showed the LC50 value of 100 ppm. Partition of ethanol extract yielded chloroform (10,52 g), n-hexane (26,58 g), and water (52,57 g) extracts. The toxicity test showed the chloroform extract to be the most toxic with LC50 of 31,97 ppm. Chloroform extract was separated by column chromatography using silica gel as stationary phase and chloroform : ethanol : water (5:4:1) as mobile phase giving three fractions. The toxicity test showed that fraction II was the most toxic with LC50 of 364,74 ppm. The phytochemical test result showed  that fraction II (the active isolate) belonged to terpene groups. Analysis using UV-Vis spectrophotometer showed three peaks at 241,  409, and 668 nm, showing the possibility of the presence of funtional groups of C-H aliphatic, C-O alkoholic and C=O, respectively